Genetic epilepsy with febrile seizures plus: definite and borderline phenotypes. Issue 3 (6th December 2011) - Thomas, R H; Johnston, J A; Hammond, C L; Bagguley, S; White, C; Smith, P E; Rees, M I
Abstract : Generalised epilepsy with febrile seizures plus (GEFS+) is the most studied familial epilepsy syndrome. However, characteristics of UK families have not previously been reported. Among the first 80 families recruited to our families study, four broad subphenotypes were identified: families with classical GEFS+; families with borderline GEFS+; families with unclassified epilepsy; and families with an alternative syndromal diagnosis. Borderline GEFS+ families shared many characteristics of classical GEFS+ families—such as prominent febrile seizures plus and early onset febrile seizures—but included more adults with focal epilepsies (rather than the idiopathic generalised epilepsies predominating in GEFS+) and double the prevalence of migraine. Thus the authors believe that a novel and robust familial epilepsy phenotype has been identified. Subcategorising families with epilepsy is helpful in targeting both clinical and research resources. Most families with GEFS+ have no identified causal mutation, and so predicting genetic homogeneity by identifying endophenotypes becomes more important.